COVID-19 INDUCED CATATONIA: A REVIEW OF THIS RARE PHENOMENON - Anvekar, Priyanka; Lohana, Petras; Mukhtadir Kalaiger, Abdul; Rashid Ali, Syed; Arti (Journal of Ayub Medical College Abbottabad, 2022)
Background: Catatonia is a psychomotor syndrome characterized by numerous clinical features, a few being stupors which is the most common sign, posturing, forced grasping, echopraxia, etc. There have been cases documented in the literature of Catatonia occurring with COVID-19. This article will focus on the complete and brief overview of catatonia observed in patients with COVID-19 infection. Methods: We outline the evidence of the pathophysiology of COVID-19 in the CNS system, the effect of the virus in inducing catatonia, and its outcome. The literature used in the article is mostly case reports from different parts of the world thus; we have generalized our review taking into consideration multiple factors. Results: In patients with COVID-19, neuropsychiatric manifestations are very commonly appreciated. Catatonia has been documented in many patients along with respiratory symptoms such as fever, shortness of breath, and cough. There are multiple etiologies associated with this presentation which have been discussed in detail in this article. In many patients, there was no history of any psychiatric illness. The timing of presenting with catatonic features was also different for different individuals. Conclusion: COVID-19 has been believed to contribute to the presentation of catatonia. There is no specific timeline between the onset of symptoms and the presence of COVID-19 infection. However, coronavirus can be responsible in a few ways for inducing catatonia in patients with or without any previous psychiatric illness. Therefore, COVID-19 should be considered as one of the major factors in this complex psychiatric disease, catatonia